Viewpoint: High-frequency phone surveys on COVID-19: Good practices, open questions. (December 2021) - Gourlay, Sydney; Kilic, Talip; Martuscelli, Antonio; Wollburg, Philip; Zezza, Alberto
Highlights: This paper provides an overview of options for the design and implementation of national phone surveys. The discussion draws on the experience with high-frequency phone surveys on COVID-19 in Africa. Recommendations are provided for phone surveys to be the mainstay in routine and crisis monitoring efforts. Abstract: Following the onset of the COVID-19 pandemic, face-to-face survey data collection efforts came to a halt due to lockdowns, limitations on mobility and social distancing requirements. What followed was a surge in phone surveys to fulfill rapidly evolving needs for timely and policy-relevant microdata for understanding the socioeconomic impacts of and responses to the pandemic. Even as the face-to-face survey data collection efforts are resuming in different parts of the world with COVID-19 safety protocols, the rapidly-acquired experience with phone surveys on the part of national statistical offices and survey practitioners in low- and middle-income countries appears to have formed the foundation for phone surveys to be more commonly implemented in the post-pandemic era, in response to other shocks and as complementary efforts to face-to-face surveys. Informed by the practical experience with the high-frequency phone surveys that have been implemented with support from the World Bank Living Standards Measurement Study (LSMS) to monitor the socioeconomic impacts of the COVID-19 pandemic, this paper provides an overview of options for the design and implementation of phone surveys to collect representative data from households and individuals. Further, the discussion identifies the requirements for phone surveys to be a mainstay in the toolkits of national statistical offices and the directions for future research on the design and implementation of phone surveys.